2016
DOI: 10.1002/14651858.cd005576.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic salt solution for peri-operative fluid management

Abstract: A new author has been added to the review team (Brad Shrum). We added three new studies which did not change the conclusions of the review. We updated the methods for the review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…This may result in central pontine myelinolysis, metabolic depression, AKI and congestive cardiac failure. Except for a statistically significant rise in the postoperative serum sodium at the 12th and 24th h, and stoppage of the infusion in one patient intraoperatively, there were no adverse effects related to the administration of 3% HTS, further outlining its safety in this cohort of patients, which are similar to the results obtained in previous studies [6, 13].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This may result in central pontine myelinolysis, metabolic depression, AKI and congestive cardiac failure. Except for a statistically significant rise in the postoperative serum sodium at the 12th and 24th h, and stoppage of the infusion in one patient intraoperatively, there were no adverse effects related to the administration of 3% HTS, further outlining its safety in this cohort of patients, which are similar to the results obtained in previous studies [6, 13].…”
Section: Discussionsupporting
confidence: 87%
“…A recent study showed that a difference of 550 ml of intraoperative fluid results in a higher incidence of complications in the group with more positive fluid balance [8]. The mean difference between patients receiving HTS and isotonic solutions is around 910 ml [6]. So, we hypothesized that the use of 3% HTS will reduce the intraoperative maintenance fluid requirement by at least 500 ml as compared to 0.9% normal saline (NS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hypertonic saline is effectual in the resuscitation of patients with hypovolemic shock [ 7 , 8 ]. It is also an alternative for volume preloading before anesthesia [ 9 ], and for perioperative fluid management [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The review collected primary outcome data on mortality and serious adverse events. Secondary outcomes included fluid balance over the study period, total volume of intravenous fluid delivered (during perioperative and recovery period), perioperative diuresis, maximum and final serum sodium concentration, durations of postoperative stay in both intensive care and in hospital, serum osmolarity and intraoperative measures of cardiac function if they were reported in the study (Shrum et al 2016).…”
Section: Objectivesmentioning
confidence: 99%